Hair and Scalp Health in Modern Lifestyle: Challenges and Natural Solutions - Kutaj, Aleksandra; Savitskaya, Tatyana (Quality in Sport, 2025)
Introduction and Purpose Hair, as epidermal appendages, serve protective, aesthetic, and psychosocial functions. Their condition reflects the health of the scalp, whose proper structure and function are essential for normal growth. Accurate diagnosis of scalp type and the selection of appropriate care methods constitute the foundation of effective trichological management. The aim of this study is to present natural methods of hair and scalp care in the light of available literature, with particular emphasis on the role of plant-derived ingredients and the importance of scalp diagnostics. Material and Methods This study was prepared using both international and Polish literature. Selected articles were reviewed from databases including PubMed, Google Scholar, EBSCO, as well as Polish- and English-language scientific sources. Description of the State of Knowledge The hair growth cycle consists of anagen, catagen, and telogen phases, and its disturbances may lead to weakening and hair loss. Structural damage results from mechanical, chemical, and thermal factors, as well as improper care practices. Increasing importance is attributed to natural preparations rich in antioxidants, micronutrients, and fatty acids, which support hair shaft regeneration and follicle function. An equally important aspect is the adjustment of care methods to the scalp type-dry, oily, normal, or sensitive-which helps maintain balance and improve hair quality. Conclusions Optimal hair condition requires a holistic approach, including scalp diagnostics, individualized care, and the use of natural preparations. Systematic and consistent therapy is essential to achieve lasting results and to support healthy hair growth.